Advantages of Combining Small and Large Groups: Implications for Second Language Education - Jacobs, George; Farrell, Thomas S. C. (Widya Mandala Catholic University Surabaya, 2019)
This paper looks at the value of second language students, teachers, and others interacting in very large groups of tens and even 100s of members of the same group. The paper begins by looking at disadvantages of these larger groups and then at their advantages, before providing advice on how to facilitate groups regardless of their sizes. This advice includes dividing resources and roles, promoting a common identity, encouraging rewards and celebrations, using groups of different sizes, taking advantage of communication technology, and paying attention to the development and use of collaborative skills. The authors’ conclusion is that very large groups can be beneficial if those involved carefully attend to the groups’ functioning, such as by dividing those very large groups into much smaller groups, including groups of 2-4 members.